2009
DOI: 10.1590/s0102-09352009000100029
|View full text |Cite
|
Sign up to set email alerts
|

Receitas bruta e líquida parcial e custo de dietas contendo polpa cítrica para suínos abatidos com 130kg de peso

Abstract: 3In memorian 4 Aluno de graduação -FCAV-UNESP -Jaboticabal, SP 1 RESUMO Avaliou-se o custo de inclusão da polpa cítrica em programa de restrição alimentar qualitativa, utilizando dados de desempenho de 36 suínos da linhagem Topigs, dos 83,7±5,1kg aos 129,8±1,9kg de peso, alimentados com dietas contendo porcentagens crescentes (0, 10, 20 e 30%) de polpa cítrica. Os animais foram abatidos aos 130kg e dos valores (R$) da carcaça foram descontados o valor de compra dos animais e o custo com alimentação, de acordo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, cellulose, hemicellulose and pectin are degraded to short-chain volatile fatty acids (AGVs), such as acetate, propionate and butyrate (Willians et al, 2001). Watanabe et al (2009) tested the inclusion of up to 30% of the citrus pulp in the diets of finishing swines and observed a linear reduction in the Loin Depth and Hot Carcass Weight. With the increase in the percentage of citrus pulp, however, such decrease was not enough to affect the percentage of lean meat.…”
Section: Animal Performance Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, cellulose, hemicellulose and pectin are degraded to short-chain volatile fatty acids (AGVs), such as acetate, propionate and butyrate (Willians et al, 2001). Watanabe et al (2009) tested the inclusion of up to 30% of the citrus pulp in the diets of finishing swines and observed a linear reduction in the Loin Depth and Hot Carcass Weight. With the increase in the percentage of citrus pulp, however, such decrease was not enough to affect the percentage of lean meat.…”
Section: Animal Performance Testmentioning
confidence: 99%
“…The costs of the ingredients of the diets to be used and the sale value of the pigs can be limiting for the adoption of alternative foods, For Watanabe et al (2009), working with qualitative feed restriction of finishing swine, concluded that the costs of the ingredients to be used can be limiting for the adoption of alternative diets. Like Fraga (2005) who found an increase in gross revenue due to the effect of qualitative feed restriction due to the improvement of the bonus index, evaluating the inclusion of rice husk in the swine diet.…”
Section: Economic Feasibility Of Including Açaí Seedmentioning
confidence: 99%
“…Silage is commonly used as a raw material in cattle and sheep nutrition with good results in terms of milk production (Piquer et al 2009) and animal growth (Alnaimy et al 2017). In the last few decades, the use of silage has extended to nutrition for monogastric animals, such as pigs (Amorim et al 2011(Amorim et al , 2014Crosswhite et al 2013;Watanabe et al 2009Watanabe et al , 2010 and chickens (Mourão et al 2008;Silva et al 2013), with no adverse growth parameters. In fish nutrition, silage has been tested in two continental fish, Oreochromis niloticus (Moreno Alvarez et al 2000) and Rhamdia quelen (Rodriguez et al 2012).…”
Section: Introductionmentioning
confidence: 99%